SARS-CoV-2: ACE inhibitors, disastrous or desirable? - Leclézio, Alexandra; Robinson, Jared; Banerjee, Indrajit (Journal of Biomedical Sciences, 2020)
Background: The world has a current total of 6,663,304 confirmed cases of COVID-19 with a death count of 392,802 deaths according to the WHO (6 June 2020). Various risk factors for the acquisition and subsequent development of deadly complications due to the virus have been established. One such risk factor is the presence of cardiovascular disease, particularly hypertension as a comorbidity. It must be noted that JNC 8 advise the use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers as first line drugs for the management of hypertension. ARDS is caused by the activation of angiotensin I, angiotensin II and AT1 receptor pathway, however stimulation of Mas receptor, MRGPR receptors, AT2 receptor and the ACE-2-angiotensin (1-7), pathways is found to be defensive. Mas receptor exerts an inhibitory effect on inflammation and cellular growth and vascular mechanisms. This research aims to examine the relationship between ACE inhibitors and the risk of COVID-19 infections with the goal of determining whether this relationship is spurious in association or whether it is causative in nature? More specifically, in this research article we will determine whether the SARS-CoV-2 virus has an affinity for ACE 2 receptors in humans. Furthermore, it will be determined whether ACE inhibitors would inhibit or facilitate an imminent COVID-19 infection in individuals as well as to determine whether patients currently using ACE inhibitors should continue or discontinue the drug therapy in order to minimize their susceptibility to acquiring COVID-19, and whether patients should start ACE inhibitor therapy if required during this pandemic. Conclusion: It is evident that ACE 2 receptors are the portal of entry for SARS-CoV-2. It is recommended that the use of RAAS inhibitors, viz ACE inhibitors and angiotensin receptor blockers is not stopped or decreased despite the ongoing pandemic as the results thereof may lead to the worsening of the patient’s comorbidity and may hasten death.